Analisis Mengenai Kependidikan pada MAS PAB 1 Sampali - Ujung, Nursholihat; Addilla, Addilla; Pasaribu, Ariyani; Nasution, Fauziah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
MAS PAB 1 Sampali is located at Jalan Pasar Hitam No. 69 Sampali, Sampali Village, Percut SEI Tuan District, Sampali Sub-District, Deli Serdang Regency, North Sumatra Province. This private school is part of a complex or entrance gate with several other schools. Established and operating since 1988, MAS PAB 1 Sampali also has the best and most competent educators, administrative staff, and school administrators in their field. Learning support activities, such as extracurricular activities, student organizations, study communities, sports teams, and libraries, also help students learn to the fullest. In addition, the school also focuses on instilling noble character and developing students' talents in sports, arts, and other extracurricular activities such as student council, boy scouts, and flag raising troop. The facilities at MAS PAB 1 Sampali are also adequate, including special rooms for counseling for students who need it.